Evaluating Local Government Policy Innovations: A Case Study of Surabaya's Efforts in Combating Stunting and Enhancing Public Health Services Quality - Arieffiani, Deasy; Ekowanti, Mas Roro Lilik (Research and Development Agency Ministry of Home Affairs, 2024)
This research aims to evaluate regional innovations in implementing Surabaya City government policies to reduce stunting rates and improve the quality of public health services. A qualitative descriptive method was used with a case study approach involving field observations and structured interviews. The research results show the success of Posyandu Prima in reducing stunting rates significantly in the last two years. The Surabaya City Government has proven effective in managing this program's human resources and budget. The active involvement of Great Surabaya Cadres (KSH) and non-governmental organizations also contributed greatly to the program's success. Cross-sector collaboration plays an important role in supporting implementation. Institutional characteristics, such as commitment to public health and ability to collaborate, also matter. Theoretically, this research shows that synergy between the parties involved and government commitment can achieve significant results in handling the stunting problem. In conclusion, the Prima Posyandu Program has proven successful in reducing stunting rates and improving the quality of public health services in Surabaya. Additionally, the collaborative efforts between community stakeholders, healthcare providers, and governmental bodies underscore the crucial role of multi-sectoral partnerships in addressing complex public health issues like stunting. This synergy fosters comprehensive approaches that combine local knowledge, resources, and policy support to effectively combat stunting and enhance the well-being of communities. Thus, the Prima Posyandu Program's success is a compelling example of how concerted action and sustained commitment can yield tangible improvements in population health outcomes.